Analysis Of The Edge Effect On Bird And Primate Distribution In The Ecological Corridor Habitat Of Mount Halimun Salak National Park (TNGHS) - Yossa Istiadi; Dolly Priatna; Wahju Widodo (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the threat of edge effects on endemic animal populations due to the presence of causeways in the TNGHS corridor habitat. Indicators of the occurrence of edge effects are characterized by the further distance of wildlife populations from sources of disturbance such as noise, light, and frequency of human activity mechanisms. Belt transect research method for population study and distribution of Javan Gibbon and Surili. Intensive Point Account (IPA) to measure the diversity index of bird species and Javan eagles. Encounter Rate is used for animal distribution studies. Results On the observation transect made along 3 km, the population density of Javan Gibbons was obtained 0.114 ind/ha, Surili 0.024 indv/ha, and Monkey 0.028 indv/ha. Bird species diversity index in 3 habitat patches each Purasari H'= 2.78 with 38 species; Garehong with 27 species, and Corridor H'= 3,087 with 27 species. The similarity of species is that there are only 7 species of birds found in the 3 habitats of the patch. As a result of primate population density and burng species similarity, it can be concluded that the cross-corridor access road area has experienced an edge effect and tends to be a bottle-neck area for the distribution of animals, especially primates.